From Schrödinger to Von Kármán: An Intriguing New Geological Structure Revealed by the Chang'e‐4 Lunar Penetrating Radar. Issue 2 (14th January 2023) - Cao, Huaqing; Xu, Yi; Xu, Luyuan; Zhang, Ling; Bugiolacchi, Roberto; Zhang, Feng
Abstract: Since early 2019, the Lunar Penetrating Radar (LPR) onboard Chang'e‐4 (CE‐4)'s Yutu‐2 rover has been gathering data relating to the subsurface structure of the Von Kármán crater within the South Pole‐Aitken Basin (SPA) on the lunar farside. Low‐frequency radar data have the potential of carrying geological information of about 300 m worth of strata below the traversed path. Forty‐two days' data have revealed a bifurcated structure within the layered structure beneath the CE‐4 surveying area for the first time, affecting the overlying reflectors between 90 and 310 m. This study suggests that, based on the morphological characteristics, thickness, depth (timing sequence) and direction of the newly found structure, its origin might be linked to the deposition of ejecta from the Schrödinger impact. The local stratigraphy is interpreted as consisting of distinct geological layers, corresponding to the superposition of ejecta from different impact craters, paleo‐regolith, and basaltic lava flows. Plain Language Summary: A radar (the Lunar Penetrating Radar, or LPR), built to look at the rocks below the surface, is presently traveling across an area of the lunar farside onboard a rover, called Yutu‐2 sent by China to shed some light on the striking difference between the Earth‐facing side of the Moon and its farside. So far, the radar has revealed layered structures interpreted as distinct volcanic flows, thus helping to unravel their history. The rover has been surveying the floor of the Von Kármán crater inside one of the oldest and largest impact structures of the Moon, the South Pole‐Aitken (SPA) Basin. By analyzing 42 lunar days of data, we found a new layer with a hunched upper surface and a relatively flat bottom inserted into a multilayered structure. Based on the morphology, thickness, depth, and direction of the new feature, we argue that its source could represent the ejecta deposition from one of the ancient lunar impact basins: Schrödinger. The subsurface structure revealed by the radar shows a complicated geologic history on the farside including multiple lava eruption events, the deposition of ejecta from different impact craters and weathering layers that develop during the quiescent stage. Key Points: The CH‐1 Lunar Penetrating Radar data of Chang'e‐4 reveals ∼300 m deep subsurface stratigraphy of the lunar farside A unique bifurcated structure that resembles an ejecta discontinuity affects the overlying and underlying strata The geologic evolution of the Von Kármán crater and the ejecta layer might be connected to the Schrödinger basin